Implementasi Kepemimpinan Transformasional Muhammad Al-Fatih dalam Pendidikan - Saputra, Dona Adi Bayu; Khozin, Khozin; Nurhakim, Mohammad (Lembaga Yasin AlSys, 2024)
This article explores the pattern of Islamic leadership by Muhammad Al-Fatih, the conqueror of Constantinople and Rome (1432-1481 CE). The success of the Ottoman Empire, particularly Muhammad Al-Fatih, reflects the struggle for Islamic educational values. The impact and legacy of Sultan Al-Fatih in the development of Islamic education are discussed, as well as leadership values relevant to the modern educational context. Muhammad Al-Fatih, an influential leader, demonstrated excellence and the fight for Islamic educational values. This article also highlights the need for learning from history, especially in the context of Islamic education amidst the moral decline of youth and current educational challenges. Through a qualitative research method of historical literature review study, this article discusses Muhammad Al-Fatih. His contribution to the understanding of Islamic leadership values opens up insights for designing a holistic and progressive education system, expected to have a positive impact on the development of education in our country.